Evaluating ex vivo toll-like receptor agonist response as a potential biomarker in equine gastric ulcer syndrome - Gustavo Ferlini Agne; Daniel Thomas Barratt; Bridget Eileen May; Mark R. Hutchinson; Joshua Holmes; Catherine Steel; Olivier Simon; Samuel Greig Evans; Andrew A. Somogyi; Benjamin W. Sykes; Samantha Franklin (The Veterinary Journal, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Packaging films prepared from hot acid vs ultrasound-assisted microwave extracted pectin: a comparative study - Chandra Mohan Chandrasekar; Michael A. Jackson; Karl E. Vermillion; Kervin O. Evans; Andre K. White; Stefanie Simon; Arland T. Hotchkiss; Pankaj Koirala; Rishabh Goyal; Shyam S. Sablani; Wei Zhao (Food Hydrocolloids, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

Interconnectivity can be as important as habitat type in explaining carbon stocks in the coastal lagoons of arid regions - Stephen Carpenter; Kostantinos A. Stamoulis; Daniel Mateos-Molina; Simon J. Pittman; Marina Antonopoulou; Himansu S. Das; Claire Evans (Science of The Total Environment, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Multi-habitat carbon stock assessments to inform nature-based solutions for coastal seascapes in arid regions - Stephen Carpenter; Claire Evans; Simon J. Pittman; Marina Antonopoulou; Ivonne Bejarano; Himansu S. Das; Mona Möller; Kate Peel; Fatin Samara; Kostantinos A. Stamoulis; Daniel Mateos-Molina (Frontiers in Marine Science, 2023)
Coastal ecosystems are integral to global carbon cycling and are increasingly recognised for their role in mitigating climate change. Within these ecosystems, the dynamics of carbon storage are diverse, varying significantly across different habitats. However, existing management strategies often focus predominantly on vegetated habitats neglecting the contributions of non-vegetated areas. We address this knowledge gap by providing a quantitative spatial assessment of carbon storage across coastal seascapes varying in plant biomass. Our comprehensive multi-habitat inventory of carbon stocks in the United Arab Emirates confirmed that mangroves are the largest carbon-storing habitat per hectare (94.3 t/ha), followed by saltmarshes (63.6 t/ha), microbial mats (51.6 t/ha), mudflats (46.8 t/ha), seagrass (32.5 t/ha), and coastal sabkha (31.0 t/ha).Mean carbon content in the top 50 cm of mangrove soils (53.9 t/ha) was similar to saltmarshes (52.7 t/ha), microbial mats (51.6 t/ha), and mudflats (46.8 t/ha). We highlight the importance of including non-vegetated habitats in carbon accounting and management strategies. Our findings suggest that a more context-specific whole-system approach is essential for guiding effective ecosystem management and designing ecologically meaningful Nature-based Solutions (NbS). Adopting this broader perspective in NbS can ensure more comprehensive conservation and restoration outcomes, which not only protect and enhance blue carbon ecosystems but also contribute to broader ecological and social benefits. This approach is pivotal for advancing our understanding of interconnected coastal ecosystems and their role in climate change mitigation.

Draft Genome Sequence of a Primate Isolate of Kazachstania pintolopesii - Steve A. James; Aimee Parker; Catherine Purse; Andrea Telatin; David Baker; Rhiannon Evans; Sandy Holmes; Simon G. P. Funnell; Simon R. Carding (Mycopathologia, 2023)
Kazachstania pintolopesii is an opportunistic mammalian pathobiont from the K. telluris species complex. No draft genomes of this species are currently available. Here, we report the first draft genome sequence of a primate isolate of K. pintolopesii (NCYC 4417).

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Comparing Rates of Linage Diversification with Rates of Size and Shape Evolution in Catarrhine Crania - Evan A. Simons; Stephen R. Frost; Katerina Harvati; Kieran McNulty; Michelle Singleton (Evolutionary Biology, 2020)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Four weeks of probiotic supplementation reduces GI symptoms during a marathon race - Jamie N. Pugh; Andy S. Sparks; Dominic A. Doran; Simon C. Fleming; Carl Langan-Evans; Ben Kirk; Robert Fearn; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2019)

Accounting for interspecific competition and age structure in demographic analyses of density dependence improves predictions of fluctuations in population size - Marlène Gamelon; Stefan J. G. Vriend; Steinar Engen; Frank Adriaensen; André A. Dhondt; Simon R. Evans; Erik Matthysen; Ben C. Sheldon; Bernt‐Erik Sæther (Ecology Letters, 2019)
Understanding species coexistence has long been a major goal of ecology. Coexistence theory for two competing species posits that intraspecific density dependence should be stronger than interspecific density dependence. Great tits and blue tits are two bird species that compete for food resources and nesting cavities. On the basis of long‐term monitoring of these two competing species at sites across Europe, combining observational and manipulative approaches, we show that the strength of density regulation is similar for both species, and that individuals have contrasting abilities to compete depending on their age. For great tits, density regulation is driven mainly by intraspecific competition. In contrast, for blue tits, interspecific competition contributes as much as intraspecific competition, consistent with asymmetric competition between the two species. In addition, including age‐specific effects of intra‐ and interspecific competition in density‐dependence models improves predictions of fluctuations in population size by up to three times.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Ecological diversification of the Australian Coptotermes termites and the evolution of mound building - Timothy R. C. Lee; Theodore A. Evans; Stephen L. Cameron; Dieter F. Hochuli; Simon Y. W. Ho; Nathan Lo (Journal of Biogeography, 2017)
Aim The Australian Coptotermes (Family: Rhinotermitidae) are a small monophyletic group of termites, some of which build mounds. In this study, we construct predicted distributions based on environmental data (niche models) for all Australian species of Coptotermes to test whether specific environmental factors have contributed to the evolution of mound‐building behaviour and whether the degree of niche similarity and degree of phylogenetic similarity are correlated. Location The Australian mainland, including the known native ranges of all Australian species of Coptotermes . Methods We estimated the phylogenetic relationships between the species of Australian Coptotermes . We then generated and compared environmental niche models in a phylogenetic framework for all study species to test niche conservation. Our analyses were based on location data from our own sampling and from the Atlas of Living Australia, genetic data from a previous study of Australian Coptotermes , and environmental data from WorldClim and ASRIS . Results We found that no environmental variable differed consistently between mound‐building and non‐mound‐building taxa and that the differences in niches between pairs of Australian species of Coptotermes are uncorrelated with time since divergence. The environmental tolerances of the Australian Coptotermes termites are more restricted by rainfall than they are by soil or temperature. Main conclusions Our results show that mound‐building behaviour has not necessarily evolved in response to similar abiotic conditions. Our results are consistent with ecological speciation leading to niche divergence since Coptotermes first arrived in Australia ~12.5 million years ago.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

When condition trumps location: seed consumption by fruit‐eating birds removes pathogens and predator attractants - Evan C. Fricke; Melissa J. Simon; Karen M. Reagan; Douglas J. Levey; Jeffrey A. Riffell; Tomás A. Carlo; Joshua J. Tewksbury (Ecology Letters, 2013)
Seed ingestion by frugivorous vertebrates commonly benefits plants by moving seeds to locations with fewer predators and pathogens than under the parent. For plants with high local population densities, however, movement from the parent plant is unlikely to result in ‘escape’ from predators and pathogens. Changes to seed condition caused by gut passage may also provide benefits, yet are rarely evaluated as an alternative. Here, we use a common bird‐dispersed chilli pepper ( Capsicum chacoense ) to conduct the first experimental comparison of escape‐related benefits to condition‐related benefits of animal‐mediated seed dispersal. Within chilli populations, seeds dispersed far from parent plants gained no advantage from escape alone, but seed consumption by birds increased seed survival by 370% – regardless of dispersal distance – due to removal during gut passage of fungal pathogens and chemical attractants to granivores. These results call into question the pre‐eminence of escape as the primary advantage of dispersal within populations and document two overlooked mechanisms by which frugivores can benefit fruiting plants.

Extinction vulnerability of coral reef fishes - Nicholas A. J. Graham; Pascale Chabanet; Richard D. Evans; Simon Jennings; Yves Letourneur; M. Aaron MacNeil; Tim R. McClanahan; Marcus C. Öhman; Nicholas V. C. Polunin; Shaun K. Wilson (Ecology Letters, 2011)

Tracking volcanic sulfur dioxide clouds for aviation hazard mitigation - Simon A. Carn; Arlin J. Krueger; Nickolay A. Krotkov; Kai Yang; Keith Evans (Natural Hazards, 2009)

Phase-reversed seabed reflections in seismic data: examples related to mud volcanoes from the South Caspian Sea - Robert J. Evans; Simon A. Stewart; Richard J. Davies (Geo-Marine Letters, 2007)

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

Prostaglandins and nitric oxide in regional kidney blood flow responses to renal nerve stimulation - Niwanthi W. Rajapakse; Rebecca L. Flower; Gabriela A. Eppel; Kate M. Denton; Simon C. Malpas; Roger G. Evans (Pflügers Archiv - European Journal of Physiology, 2004)

Nitric oxide in responses of regional kidney perfusion to renal nerve stimulation and renal ischaemia - Gabriela A. Eppel; Kate M. Denton; Simon C. Malpas; Roger G. Evans (Pflügers Archiv - European Journal of Physiology, 2003)

CD2F-10: a new member of the CD2 subset of the immunoglobulin superfamily - Janet A. Fennelly; Bela Tiwari; Simon J. Davis; Edward J. Evans (Immunogenetics, 2001)